Interest And Motivation Analysis Of Lecturer In State Polytechnic Of Balikpapan To Learn English (Qualitative-Quantitative Research) - Lilik Damayanti; Elisabeth Milaningrum (JST (Jurnal Sains Terapan), 2016)
The purpose of this study is (1) to determine the interest and motivation of lecturer in State Polytechnic of Balikpapan to English; (2) to determine the relationship between interest and motivation toward their result in English learning activity. There are two data that used in this research, the first data is taken from the result of English learning activity, and the second data is taken from questionnaires which given to the 20 respondent. Distribution of questionnaires is given to the lecturer in State Polytechnic of Balikpapan. The questionnaires consist of several questions that can determine the interest and motivation to learn or involve in English learning activity. And the data from English learning activities is used to analyze whether there is any relationship between them. The analysis of data is given through the descriptive method. The results showed that (1) There is an interest of the lecturer in State Polytechnic of Balikpapan to follow the English training, it shows with the frequency of “always” in 94 frequency as the biggest one than other, but also there are a few of them has no interest to follow that training. (2) There is a motivation of the lecturer in State Polytechnic of Balikpapan to learn English but they have difficulties to understand the materials. (3) There is a well-motivated with Low-achievement Category for the lecturer of State Polytechnic of Balikpapan, means that their lower comprehend ability and score are not caused of their lower interest, but it caused of their former skill is not good enough.